Overcoming the Length of Waiting Time of Inpatient Drug Service in Pharmaceutical Installation in Hospital X - Sindy Sabatina; Tita Hariyanti; Dewi Lelonowati; Sujiono Sujiono (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Inpatient drug service in the pharmaceutical installation in Hospital X has not met the (MSS) Minimal Service Standard. There is delay in delivering the drug by 3%, while according to the standard, it should be 0%. Objective Case study was conducted by the researcher aiming to know the factors affecting the length of time of inpatient drug service in the pharmaceutical installation and its solution alternative. Method: The research was carried out qualitatively, in which the data was collected through unstructured interview, FGD (Focus Group Discussion) and observation. The participants involved in the research was 30 people. Result are The research data was analyzed using “5 why” by grouping the 5M factors obtained consisting of man, method, machine, material and management into 3 main factors as the causes of the long waiting time. The main factors causing the long waiting time were the absence of time target for each service flow established by the management, incomplete SOP (Standard Operational Procedure), the absence of service flow in accordance with the implementation in the field as well as ineffective and inefficient inpatient pharmaceutical installation layout. Furthermore, in order to obtain the solution, NGT (Nominal Group Technique) was employed to do the assessment obtaining 3 solutions including completing the SOP and designing the inpatient drug service flow in pharmaceutical installation, establishing the target time for each service flow by the management, and designing more effective and efficient layout for the pharmaceutical installation.